Perbedaan Metode Pengajaran Bagi Anak - Anak dengan Disabilitas di SD Methodist 3 Palembang - Nurjanah, Nurjanah (Journal of Innovation in Teaching and Instructional Media, 2024)
This research aims to identify and analyze differences in teaching methods for children with disabilities at the Methodist 3 Palembang Elementary School and normal students, as well as factors that influence the effectiveness of inclusive learning. The research method used is a qualitative descriptive study, with in-depth interviews and observations of teachers, students and education staff in public schools that implement an inclusion system. The research results show that teaching methods for children with disabilities require a more individualized approach, the use of specific learning aids, and adaptation of teaching materials to accommodate their special needs. The main differences identified are in the aspects of teaching strategies, communication approaches, as well as supporting facilities and resources used in learning. The novelty of this research lies in the comparative analysis of learning approaches for children with disabilities with and without structured inclusive programs, as well as the impact of these approaches on student development. This research contributes to providing recommendations for schools, educators, and policy makers to improve the implementation of inclusive education through special training for teachers, developing adequate facilities, and designing an inclusive curriculum.